Cyclones Idai and Kenneth - OCHA (United Nations Office for the Coordination of Humanitarian Affairs, 2019)
In March and April 2019, Southern Africa was hit by two subsequent cyclones that left a trail of destruction in their path, and close to 2.2 million people in need urgent assistance in Mozambique alone. On the night of 14 to 15 March Tropical Cyclone Idai made landfall near Beira City, Sofala Province, in central Mozambique. The cyclone brought torrential rains and winds to Sofala, Zambezia, Manica and Inhambane provinces. Cyclone Idai continued across land as a Tropical Storm and hit eastern Zimbabwe with heavy rains and strong winds. The storm caused high winds and heavy precipitation in Chimanimani and Chipinge districts causing riverine and flash flooding and subsequent deaths, destruction of livelihoods and properties. Idai left more than 600 people dead and an estimated 1.85 million people in need in Mozambique alone. On 24 April, Tropical Cyclone Kenneth passed north of the Comoros Islands, hitting the northern island of Ngazidja. On the evening of 25 April, the cyclone made landfall in Mozambique between the districts of Macomia and Mocimboa da Praia in Cabo Delgado province. With wind gusts of up to 220km/h, Tropical Cyclone Kenneth became the strongest cyclone to ever hit the African continent. Cyclone Kenneth left 374,000 people in need. Tropical Cyclone Kenneth reportedly caused three deaths, at least 20 injuries and extensive damage to houses across the archipelago. Preliminary estimates indicate that at least 1,000 people were displaced, most of them children. While assessments are ongoing, initial reports from the Comoros indicate that several villages were flooded due to sea surges and broken dykes, and that power was cut in multiple locations. Roads have reportedly been damaged and cut off by fallen trees, while telephone poles are down in multiple locations. Latest updates on the response can be found here. It is the first time in recorded history that two strong tropical cyclones have hit Mozambique in the same season. Cyclone Idai As of 9 April, the official death toll caused by Cyclone Idai stands at 602 people, with more than 1,600 people injured, according to the Government. Many people are displaced, and communicable diseases are on the rise. Of particular concern are cholera and malaria. An oral vaccination campaign reached over 800,000 people by early April 2018. Many schools are damaged or used as shelter for displaced people. Humanitarian partners continue to call for any relocations out of schools or elsewhere to be safe, dignified and voluntary. In figures People in need 1.85M People targeted 1.72M Funding needed $282M Cyclone Kenneth The cyclone hit Mozambique more north than Cyclone Idai, with Quissanga, Macomia, and Ibo districts in Cabo Delgado hardest-hit, according to preliminary government reports. At least 45 deaths have been reported and 18,029 people were initially reportedly displaced, according to the National Disaster Management Institute (INGC). Cyclone Kenneth made landfall at the end of the rainy season, when river levels were already high, increasing the risk of river flooding. Humanitarian needs in Mozambique have sky-rocketed, and the humanitarian response will need to rapidly scale-up while capacity and funding are limited. In figures People in need 374K People targeted 374K Funding needed $104M On 16 March, Cyclone Idai hit eastern Zimbabwe with heavy rains and strong winds. The storm caused high winds and heavy precipitation in Chimanimani and Chipinge districts causing riverine and flash flooding and subsequent deaths, destruction of livelihoods and properties. The homes of at least 4,000 households are destroyed or currently uninhabitable. The seven districts affected by Cyclone Idai- Chipinge, Chimanimani, Buhera, Bikita, Mutare, Gutu, and Chiredzi - multisectoral support will be required to speed recovery. The livelihoods of over 270,000 people across these districts has been affected. Those lviing in Chipinge and Chimanimani districts are worst hit. In early March, heavy rains and flooding linked to Cyclone Idai killed 60 people, displaced nearly 87,000 people and affected nearly 870,000 persons. The Government of Malawi declared a ‘state of disaster’ on 8 March and subsequently launched a Flood Response Plan and Appeal on 28 March to support life-saving humanitarian interventions in 15 affected districts. Humanitarian partners and the Government of Malawi have reached over 400,000 persons with immediate life-saving relief support which includes food, medicine, shelter, protection services and other non-food-items such as water, sanitation and hygiene supplies. A Post Disaster Needs Assessment (PDNA) has been undertaken by the Malawi Government, UN, World Bank and European Union to assess damages, losses and priority recovery needs and costs. The data and information collected will inform the Government’s recovery plan.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; climate change / mudanças climáticas; natural disasters / desastres naturais

Policy analysis Food security, nutrition, climate change resilience, gender and the small-scale farmers Mozambique - Care; ActionAid (ActionAid and Care, 2017)
The analysis covers both national specific policies and those policies and commitments that the Government of Mozambique has signed as part of global collective efforts. The analysis aims to become a baseline to better understand the policy gaps and implementation challenges in in FNS and CCR towards women and smallholders in Mozambique. The main purpose of this analysis is to become useful source and instrument in the implementation of CARE Mozambique Advocacy Strategy, and also for the Government of Mozambique, donors and civil society organizations, to better identify the challenges for a more effective investment in gender transformative, climate resilient and nutrition smart agriculture.
Keywords: *snowball; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; agriculture / agricultura; climate change / mudanças climáticas